Board credit committee intangibles and risk management of banks - Ibrahim, Murtala Aliyu; Md Yusof, Mohd ‘Atef (Opción, 2019)
The purpose of this paper is to examine the association between Board Credit Committee Intangibles (BCC) and Credit Risk Management (CR) of the Sub-Saharan African banks. Data on 37 Sub-Saharan African (SSA) banks were collected for empirical testing. The result shows a significant association between BCC and CR. In conclusion, the profitability of sub-Saharan African banks is negatively associated with the credit risks of the banks. Statistically, the overall regression result in all three variants of the measurement of credit risk is significant. Thus, there is an association between the explanatory variable and the dependent variable of the study.